Seat belt use among rear passengers: validity of self-reported versus observational measures - Schievano Elena; Marchesan Maria; Fedeli Ugo; Zambon Francesco; Ferro Antonio; Spolaore Paolo (BMC, 2008)
Abstract Background The effects of seat belt laws and public education campaigns on seat belt use are assessed on the basis of observational or self-reported data on seat belt use. Previous studies focusing on front seat occupants have shown that self-reports indicate a greater seat belt usage than observational findings. Whether this over-reporting in self reports applies to rear seat belt usage, and to what extent, have yet to be investigated. We aimed to evaluate the over-reporting factor for rear seat passengers and whether this varies by gender and under different compulsory seat belt use conditions. Methods The study was conducted in the Veneto Region, an area in the North-East of Italy with a population of 4.7 million. The prevalence of seat belt use among rear seat passengers was determined by means of a cross-sectional self-report survey and an observational study. Both investigations were performed in two time periods: in 2003, when rear seat belt use was not enforced by primary legislation, and in 2005, after rear seat belt use had become compulsory (June 2003). Overall, 8138 observations and 7902 interviews were recorded. Gender differences in the prevalence of rear seat belt use were examined using the chi-square test. The over-reporting factor, defined as the ratio of the self-reported to the observed prevalence of rear seat belt use, was calculated by gender before and after the rear seat belt legislation came into effect. Results Among rear seat passengers, self-reported rates were always higher than the observational findings, with an overall over-reporting factor of 1.4. We registered no statistically significant changes over time in the over-reporting factor, nor any major differences between genders. Conclusion Self-reported seat belt usage by rear passengers represents an efficient alternative to observational studies for tracking changes in actual behavior, although the reported figures need to be adjusted using an appropriate over-reporting factor in order to gain an idea of genuine seat belt use.